The Influence of Nonformal Education to The Religious Understanding on Learning Group of People in Sunday Morning Madani Community in Bojonegoro Regency - Tari Yono; Rahmat Arofah Hari Cahyadi (Studia Religia : Jurnal Pemikiran dan Pendidikan Islam, 2017)
This study aims to explore what underlies the Influence of Non-formal Education on the understanding of religion in the congregation of early morning "Madani Community" in Bojonegoro, the quantitative approach, how far the understanding of the congregation can engage and understand the religion of Islam. The first variable is "Non-formal education" as the independent variable and the second variable is "Understanding religion" as the dependent variable. The problem needs to be studied because the author realizes that the condition of society is good if all parties have concern for the society environment where education is a requirement, the human key to living side by side in the community environment is located. Therefore, the author pursues the theoretical and empirical. Theoretically studying some sources of literature, while empirically conducting field research, by using methods: observation, interview, documentation, and questioner. The result from this study found, at 5% significance level at N = 60 indicates the number 0.254, while the value RXY obtained is: 0.421 Thus the RXY obtained is greater than the price of "r" in the 5% Significant Tables. While at a significant level of 1% at N = 60 indicates the number: 0.330, while the RXY value obtained is 0.421. Then RXY obtained is greater than the price of "r" in the table significant level 1%. Population in this study is the congregation religious learnig community Sunday morning to Civil Society amounted to 750 worshipers. While the sample are 60 people joining to the learning. While the data analysis with Random Sampling is statistic.  Keywords: Influence, Non-formal Education, Understanding, Community